PENGARUH PEMBERIAN PUPUK KOTORAN KAMBING DAN ATONIK TERHADAP PERTUMBUHAN SETEK DAUN MAHKOTA NENAS (Ananas comusus L. Merr) KUALU PADA MEDIA GAMBUT - Mardaleni (DINAMIKA PERTANIAN, 2019)
The Kualu pineapple propagation technique uses crown bud cuttings which is made as a pineapple plant propagation material for peat media that is added with goat manure and several concentrations of Atonic. The aim is to obtain an effective source of cutting material for the procurement of Kualu pineapple seedlings cultivated on peat soil. This research used a Completely Randomized Design (CRD) factorial with two factors. First factor was the dose of goat manure at levels 0, 10, 20, and 30 g/polybag dan second factor was various atonic concentrations at levels 0, 2, 4, and 6 ml/L. The data were statistically analyzed and further tested for honest real difference (BNJ) at the 5% level. The results obtained from the interaction of the two treatment factors were significantly different to the time of shoot emergence and the percentage of shoot life. There was no significant difference in seedling height and number of leaves, as well as the main effect of each treatment. Crown shoot cuttings planted on peat media added 20 g/polybag of goat manure and 4ml/l Atonic obtained a better source of cutting material to be used as a source of seeds than others. The success of obtaining seeds from crown leaf cuttings sources through this research has answered that crown leaf cuttings have potential and great opportunity to be developed.